Micro-mechanical and tribological behavior of Al/SiC/B4C/CNT hybrid nanocomposite - A. Nirala; S. Soren; Navneet Kumar; Mohammad Amir Khan; Saiful Islam; Nadeem A Khan (Scientific Reports, 2023)
Abstract The aluminum nanocomposite is fabricated through squeeze stir casting method where CNT, SiC/B4C powder has been used as a reinforcement in an aluminum matrix. Squeeze action in stir casting opted due to proper reinforcement of 2 vol% of CNT in the matrix. The boron carbide and silicon carbide have been added by 8 and 12 vol% in the matrix. Uniform distribution of reinforcement and phase analysis has been shown by scanning electron microscopy (SEM) and XRD analysis. The formation of intermetallic compounds like Al3BC and Al4C3, dislocation forests, and the interaction of the reinforcement with the matrix are all confirmed by transmission electron microscopy (TEM). The micro-mechanical behavior of aluminum nanocomposites was investigated using nano indentation. The nano hardness, Vickers hardness, and Young's modulus of 12 vol% B4C compared with 12 vol% of SiC are increased by 12%, 23%, and 16%, respectively, and the same trend has been observed for the 8 vol% B4C reinforced composite. The model analysis for Young's modulus has been done and the experimental value for the modulus of elasticity of the composite are validated and not find such differences significantly. The surface topography was determined, furrow scratches and wear scars, and it was discovered that B4C reinforced composites have reduced stripping pits inside the wear marks, as well as lower wear width and depth. Wear analysis is essential because abrasive encounters result in substantial damage owing to larger pits and bigger wear scars.